2009
DOI: 10.1212/wnl.0b013e3181a60a58
|View full text |Cite|
|
Sign up to set email alerts
|

Association between late-life body mass index and dementia

Abstract: Higher baseline body mass index (BMI) and slower declining BMI in late life are associated with a reduced risk of dementia, suggesting that low BMI or a faster decline in BMI in late life may be preclinical indicators of an underlying dementing illness, especially for those who were initially overweight or obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
156
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(180 citation statements)
references
References 38 publications
17
156
2
5
Order By: Relevance
“…Previous studies have shown that higher midlife BMI increases risk for the clinical diagnosis of AD (28)(29)(30), but this effect is diminished or even reversed in latelife (29)(30)(31)(32)(33). A similar pattern is evident in the ex vivo literature.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that higher midlife BMI increases risk for the clinical diagnosis of AD (28)(29)(30), but this effect is diminished or even reversed in latelife (29)(30)(31)(32)(33). A similar pattern is evident in the ex vivo literature.…”
Section: Discussionsupporting
confidence: 61%
“…However, many of these studies are limited to weight trajectories in old age, and might be prone to reverse causality because dementia and preclinical dementia might cause weight loss (1,20). Therefore, to study weight and weight change as risk factors for dementia outcomes it has been proposed that midlife weight and changes in midlife into old age may be more appropriate (21). The few studies covering weight in both midlife and old age have been criticized for not taking into account baseline weight, and therefore one cannot disentangle if it is weight change per se or baseline weight, or even an interaction between the two which matters most regarding dementia risk (1).…”
Section: Introductionmentioning
confidence: 99%
“…Lower total and LDL cholesterol have indeed been associated with a poor prognosis in the ischemic stroke [93] and in elderly individuals, as observed above, this profile may increase the risk for overt dementia. Increased body mass index (BMI) in middle life appears to be a risk factor for latter development of cognitive decline and AD, but in late life the burden of cerebral amyloid and tau is associated with lower BMI in cognitively normal and MCI subjects [94][95]. These facts could contribute to the inconsistent results regarding the benefits of statins on prevention and treatment of AD, despite in vitro and animal studies demonstrating an effect in decreasing A formation [96].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%